2011
DOI: 10.1590/s1516-80342011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Interferências de estímulos visuais na produção escrita de escolares ouvintes sem queixas de alterações na escrita

Abstract: OBJETIVO: Verificar a influência de estímulos visuais na produção escrita de escolares do ensino fundamental sem queixas de alterações de leitura e escrita. MÉTODOS: Participaram 25 crianças sem queixa de leitura e escrita, que cursavam a 3ª e 4ª série (4º e 5º ano atuais) do ensino fundamental de uma escola pública. Adotaram-se como critérios de inclusão: respostas a 20 dBNA nas frequências de 500 Hz a 4 kHz na triagem auditiva; frequentar a referida escola por dois anos e possuir nível alfabético ou ortográf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
2
0
4

Year Published

2012
2012
2015
2015

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 23 publications
(18 reference statements)
0
2
0
4
Order By: Relevance
“…In the fifth and sixth grades of elementary school, there was a high incidence of spelling errors in both groups involving category LI, which is characterized by multiple representations. Other studies also found greater occurrence of errors related to multiple representations (23) . This type of error was shown to be more common in writing, once they require more complex knowledge and once contextual and morphosyntactic rules are needed (11) .…”
Section: Discussionmentioning
confidence: 84%
“…In the fifth and sixth grades of elementary school, there was a high incidence of spelling errors in both groups involving category LI, which is characterized by multiple representations. Other studies also found greater occurrence of errors related to multiple representations (23) . This type of error was shown to be more common in writing, once they require more complex knowledge and once contextual and morphosyntactic rules are needed (11) .…”
Section: Discussionmentioning
confidence: 84%
“…Entender o processo de aquisição da linguagem escrita, identifi cando recursos facilitadores pode ser uma importante ferramenta tanto em âmbito clínico quanto educacional (Casemiro et al, 2011). Sob essa perspectiva, este estudo objetivou investigar a infl uência de diferentes estímulos visuais na produção escrita de escolares com e sem queixas de alterações na escrita.…”
Section: Discussionunclassified
“…Para a realização das produções escritas foi utilizada uma fi gura de ação e quatro fi guras em sequência (Casemiro, Ribeiro, Matta, Soares, & Cárnio, 2011).…”
Section: Provas Experimentaisunclassified
See 2 more Smart Citations